2015
DOI: 10.1093/eurheartj/ehv202
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced right ventricular dysfunction is associated with ventricular arrhythmias in endurance athletes

Abstract: Among athletes with normal cardiac function at rest, exercise testing reveals RV contractile dysfunction among athletes with RV arrhythmias. RV stress testing shows promise as a non-invasive means of risk-stratifying athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
87
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(100 citation statements)
references
References 29 publications
3
87
0
8
Order By: Relevance
“…There is growing appreciation that right ventricular (RV) dysfunction is related to adverse outcomes [1113]. RV remodeling (larger RV mass and volumes) and impaired systolic and diastolic function have been documented in overweight and obese adults [1417].…”
Section: Introductionmentioning
confidence: 99%
“…There is growing appreciation that right ventricular (RV) dysfunction is related to adverse outcomes [1113]. RV remodeling (larger RV mass and volumes) and impaired systolic and diastolic function have been documented in overweight and obese adults [1417].…”
Section: Introductionmentioning
confidence: 99%
“…Le ventricule droit est plus concerné que le gauche. Ses altéra-tions fonctionnelles plus nettes sont de plus associées à une dilatation qui persiste quelques heures après l'effort [20]. Le ventricule droit a été pendant longtemps « l'oublié » de la cardiologie du sport.…”
Section: La Fatigue Myocardiqueunclassified
“…Pourtant sa physiologie à l'effort diffère de celle du ventricule gauche. En effet, la contrainte hémody-namique imposée au ventricule droit est proportionnellement plus importante que celle du ventricule gauche [20]. Or, le ventricule droit du fait de son origine embryologique différente, de sa fonction basale (éjecter le sang dans la circulation pulmonaire pour son oxygénation) simple, et de sa paroi mince peu musclée est clairement moins bien armé que le ventricule gauche pour répondre aux contraintes d'un effort intense et prolongé [1].…”
Section: La Fatigue Myocardiqueunclassified
See 1 more Smart Citation
“…Some studies have found RV and right atrium (RA) enlargement in elite athletes (Henriksen et al, 1996; Erol and Karakelleoglu, 2002). While in recent years participation in endurance sports has increased, several concerns have been raised about the harmful effects these sports may have on cardiac morphology and function and the risk of cardiac arrhythmias (Calvo et al, 2012; La Gerche et al, 2015). …”
Section: Introductionmentioning
confidence: 99%